2007
DOI: 10.14429/dsj.57.1751
|View full text |Cite
|
Sign up to set email alerts
|

Flame-retardant Cotton Fabric Through Graft Copolymerisation

Abstract: In an attempt to impart flame-retarding properties to the cotton fabric, post-grafting phosphorylation reactions on grafted cotton fabric were carried out. Photochemical graft copolymerisation of 4-vinyl pyridine (4-VP) onto cotton fabric using benzophenone as photosensitiser was carried out. Maximum percentage of grafting Pg, (18.50 %) was obtained under optimum conditions; irradiation time 75 min, 0.5 ml of benzophenone, [4-VP]=748.71 x 10 -2 mole/l and 5 ml of water in the reaction mixture. Aliphatic alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…At higher monomer concentrations, the homopolymerization increases preferentially resulting in hindered monomer diffusion into grafting sites and hence the grafting percent decreases. Also, 4-VP is wasted in the side chain reactions because of its high monomer-transfer value (CM= 7±2⋅10 -4 ), thereby decreasing percentage of grafting [38].Similar observations have also been reported by M. Nasef et al while grafting styrene onto fluorinated polymers [39].…”
Section: Effect Of Monomer Concentrationsupporting
confidence: 80%
“…At higher monomer concentrations, the homopolymerization increases preferentially resulting in hindered monomer diffusion into grafting sites and hence the grafting percent decreases. Also, 4-VP is wasted in the side chain reactions because of its high monomer-transfer value (CM= 7±2⋅10 -4 ), thereby decreasing percentage of grafting [38].Similar observations have also been reported by M. Nasef et al while grafting styrene onto fluorinated polymers [39].…”
Section: Effect Of Monomer Concentrationsupporting
confidence: 80%
“…Kandola et al [90] studied the influence of treatment of flame retardant to cotton on the mechanism of cotton pyrolysis. Photochemical grafting of 4-vinyl pyridine onto cotton fabric for imparting flame retarding properties has been reported [91]. Nakanishi et al [92,93] studied thermal degradation of cotton as well as flame retarded cotton and revealed that flame retardant cotton samples show extremely reduced amount and fewer numbers of gas products compared with untreated samples.…”
Section: Current Trends In Fashion Technology and Textile Engineeringmentioning
confidence: 99%
“…4-Vinyl pyridine has been used as fl ame retardant with benzophenone as photoinitiator for grafting onto cellulose fabrics using UV radiation technique. The thermogravimetric analysis (TGA) of the grafted fabrics showed lower decomposition temperatures with slight increase in char yield (Kaur et al ., 2007a ). Methacrylamide has also been grafted onto cotton with the use of low energy UV irradiation technique to introduce functionalities that can react with phosphorus-containing compounds to impart fl ame retardancy.…”
Section: (C) Flame Retardancy With Sulfur Derivativesmentioning
confidence: 99%